Migration and Remittances: Assessing Their Role in Socioeconomic Development in Nepal (2000–2023) - Dhakal, Chuda Prasad; Dhungana, Purna; Dhakal, Abbal; Dhakal, Aviral; Dhakal, Apekshya (Journal of Development Review, 2025)
From 2000 to 2023, this study examines how migration and remittances impact Nepal's socio-economic development. This study employs quantitative approaches such as regression analysis and trend assessment to investigate the implications of remittances on GDP growth, poverty alleviation, and economic stability. According to its findings, remittances contributed to an average of 25% of Nepal’s GDP during the survey years, leading to a major decrease in poverty by increasing household incomes and enabling access to education and healthcare. On the other hand, the study does point out challenges, including economic vulnerabilities resulting from excessive dependence on remittances and susceptibility to changes in the global economy. Policy recommendations emphasize strategic economic diversification and the productive use of remittances.